HUBUNGAN LINGKAR KEPALA DAN PERKEMBANGAN BAYI DI POLI BAYI & TUMBUH KEMBANG RSUP PROF. DR. R. D. KANDOU - Thezar, Dennis; Masloman, Nurhayati; Mandei, Jose M. (e-CliniC, 2016)
Background: Around 10% of the world’s children have delayed development. Head circumference is used as one of the indicator to identify neurological impairment and to detect the cause of developmental delay. Yet, microcephaly or macrocephaly are not always indicated a delayed development on children. Objectives: To find out the overview of head circumference and child’s development in the Child Development Center of Kandou Public Hospital and to determine the relation between both of it. Methods: This study is an analytical cross-sectional study. Data were collected with head measurement and KPSP (Kuesioner praskrining perkembangan) to assess development in the Growth and Development Clinic of Kandou Public Hospital from November 2015 to January 2016. The data were analyzed using Fisher’s exact statistical test. Results: From 34 subjects who qualified the inclusion criteria: 50% of the subjects are male, most subjects were using the third month KPSP, there are 97.1% subjects with normal head circumference, 88.2% with normal development, and the study is not statistical significant with Fisher’s exact test (p = 0.882). Conclusions: There is no significant relation between head circumference and development. Most of the infants have normal head circumference and development.Keywords: Head circumference, development, KPSPLatar Belakang: Anak-anak dengan keterlambatan perkembangan secara umum meliputi 10% anak-anak di seluruh dunia. Ukuran lingkar kepala adalah salah satu indikator yang umum diperiksa untuk mengidentifikasi kelainan neurologis dan menyingkirkan penyebab keterlambatan perkembangan. Namun, mikrosefali atau makrosefali belum tentu menandakan penyimpangan perkembangan pada anak. Tujuan: Untuk mengetahui gambaran lingkar kepala dan perkembangan bayi di Poli Bayi & Tumbuh Kembang RSUP Prof. Dr. R.D. Kandou serta hubungan antara keduanya. Metode: Penelitian ini merupakan penelitian analitik potong lintang. Data dikumpulkan dengan cara pengukuran lingkar kepala dan KPSP (Kuesioner praskrining perkembangan) untuk penilaian perkembangan di Poli Bayi & Tumbuh Kembang RSUP Prof. Dr. R.D. Kandou dari November 2015 hingga Januari 2016. Analisa data menggunakan uji statistik Fisher’s exact. Hasil: Dari 34 subjek yang memenuhi kriteria inklusi: 50% berjenis kelamin laki-laki, terbanyak menggunakan KPSP 3 bulan, 97,1% dengan lingkar kepala normal, 88,2% dengan perkembangan normal, dan penelitian ini tidak signifikan secara statistik dengan uji Fisher’s exact (p = 0,882). Kesimpulan: Tidak terdapat hubungan yang bermakna antara lingkar kepala dan perkembangan. Sebagian besar bayi memiliki ukuran lingkar kepala dan perkembangan yang normal.Kata kunci: Lingkar kepala, perkembangan, KPSP